The Publications Committee - Team, Editorial (South African Journal of Enology and Viticulture, 2017)
The Publications Committee would like to express their thanks and appreciation to the following experts by whom some of the articles in Volume 18 No. 1 and Volume 18 No. 2 were reviewed.